A mechanistic study of in situ chemical cleaning-in-place for a PTFE flat sheet membrane: fouling mitigation and membrane characterization. Issue 3 (15th March 2016) - Lee, Eui-Jong; An, Alicia K. J.; Hadi, Pejman; Yan, Dickson Y. S.; Kim, Hyung-Sook
Abstract: This study aimed at unfolding the role and mechanisms of chemically enhanced cleaning-in-place (CIP) regimes in fouling control of polytetrafluoroethylene (PTFE) made flat sheet (FS) membrane bio-reactors (MBRs). The trans-membrane pressure (TMP) was successfully maintained below 10 kPa using a daily CIP regime consisting of 100 to 600 mg l −1 of NaOCl and cake layer resistance control was shown to be critical for effective high-flux MBR operation. In contrast, in the control unit without the CIP, the TMP exceeded 35 kPa at a flux of 40 LMH. The extracellular polymeric substances associated with proteins (EPSprotein ) were also controlled effectively with a daily application of the CIP to the fouled membrane. Moreover, the CIP prompted a thinner and looser bio-cake layer on the membrane surface, suggesting that in situ CIP can be a favorable method to control FS membrane fouling at high-flux MBR operation.